PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM DUNIA PENDIDIKAN - Rifanfatoni, Rifan; Natjma Nur Aulia Maghfiroh; Alfa Reza, Muhammad Yoga; Bahtiyar, Muhammad Diki; Taufiqurrohman, M. Imam; Mahir Putra, Muhammad Nasyith (Nawasena Bhakti, 2025)
The advancement of digital technology in the era of the Industrial Revolution 4.0 and Society 5.0 encourages the integration of Artificial Intelligence (AI) into the field of education. One of its most prominent implementations is through the use of ChatGPT, which functions as a virtual assistant to support the learning process. This technology offers significant potential to enhance learning effectiveness, including providing broad access to information, aiding in the understanding of complex concepts, and encouraging student creativity and collaboration. However, observations of 10th-grade students at SMKN 4 Bojonegoro revealed a low level of understanding regarding the fundamental concepts and ethical use of AI. Most students perceive AI merely as a tool to complete assignments, without recognizing its strategic potential or ethical risks. To bridge this gap, a community service activity was carried out through four main stages: counseling, training, hands-on demonstration, and reflection. The implementation method used an educational approach based on direct practice, combining interactive lectures, ChatGPT training, distribution of digital educational materials, and evaluation through pre-test and post-test surveys. The evaluation was conducted on 20 student respondents. The results showed a significant increase in students' understanding and perception: from 20% of students previously unfamiliar with AI, to 100% stating that AI is beneficial in the learning process. This activity demonstrates that an educational approach based on hands-on practice is effective in fostering digital literacy and wise attitudes in the use of technology in vocational secondary education environments.